2019
DOI: 10.1002/mrd.23267
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐body exposure to cigarette smoke alters oocyte miRNAs expression in C57BL/6 mice

Abstract: Cigarette smoke is toxic for the female reproductive system with particular reference to the ovary. The purpose of the study was to investigate if the microRNAs (miRNAs) pattern could be altered by cigarette smoke exposure in mouse oocytes. For this purpose, C57BL/6 mice were whole‐body exposed to three cigarettes daily, 7 days/week, for 2 or 4 months by a specific rodent ventilator. Mice were then superovulated and oocytes collected. MII oocytes pools obtained by single animals were deprived of cumulus cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…[ 40 ] Budani et al suggested that cigarette‐smoke‐induced ovarian toxicity and aberrant expression of miRNAs were related to adverse pregnancy outcomes. [ 41 ] However, there have been few studies demonstrating the effect of miRNAs on the male reproductive system following exposure to CS. In this study, miRNA expression profiles of four datasets were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Budani et al suggested that cigarette‐smoke‐induced ovarian toxicity and aberrant expression of miRNAs were related to adverse pregnancy outcomes. [ 41 ] However, there have been few studies demonstrating the effect of miRNAs on the male reproductive system following exposure to CS. In this study, miRNA expression profiles of four datasets were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Control mice are exposed to room air only for the same time period. The exposure timing is the same as that used in our previous work (Budani et al., 2019). It is important to start the exposure when all mice have been transferred into the exposure chamber.…”
Section: Commentarymentioning
confidence: 99%
“…It is well known that active smoking and SHS exposure can lead to decreased sperm quality (Alkhaled et al, 2018;Sobinoff et al, 2014), follicular destruction, oocyte dysfunction (Budani & Tiboni, 2017;Budani et al, 2019;Sobinoff et al, 2011;Sobinoff et al, 2012;Sobinoff et al, 2013), and even abortion and stillbirth (George et al, 2006). However, the effects of THS and its components on reproductive health have been reported in only a few related studies.…”
Section: Ths Exposure On the Reproductive Systemmentioning
confidence: 99%